Fracture of the temporal bone in patients with traumatic brain injury - Secchi, Myrian Marajó Dal; Moraes, Juliana Furno Simões; de Castro, Fabrício Barbosa (Arquivos Internacionais de Otorrinolaringologia, 2012)
Introduction: The fractures in the temporal bone are lesions that are observed in patients with traumatic brain injury (TBI). The computed tomography of high-resolution (CT) allows evaluating the fracture and the complications.Objective: Evaluate patients with TBI and temporal bone fracture.Way of study: Retrospective study.Method: Were evaluated 28 patients interned by TBI with clinical evidence and/or radiologic from temporal bone fractures.Results: The age ranged from 3 to 75 years. The most affected side was the right side 50% (n = 14), left side 36% (n = 10) and both sides 14% (n = 4). The etiology of the trauma was the falling 25% (n = 7), accidents with motorcycles and bicycles 21% (n = 6), physical aggression 14% (n = 4), running over 11% (n = 3), fall of object 4% (n = 1) and other causes 25% (n = 7). The clinical signs were: Otorrhagia 78%, otalgia 11% (n = 3), otorrhea 7% (n = 2), facial paralysis 7% (n = 2) and hearing loss 7% (n = 2). The otoscopic findings: otorrhagia 57% (n = 16), laceration of external auditory canal 36% (n = 10), hemotympanum 11% (n = 3), normal 7% (n = 2) and Battle signal 7% (n = 2). The findings for CT of skull were: with no alterations 54% (n = 15) and temporal fracture 7% (n = 2) and the CT of temporal bones were: line of fracture 71% (n = 20), opacification of the mastoid 25% (n = 7), glenoid cavity air 14% (n = 1), dislocation of the ossicular chain 7% (n = 2) and veiling of the middle ear 4% (n = 1).Conclusion: Patients with TBI must be submitted to the otorhinolaryngological evaluation and imaging, for the early diagnosis of the complications and treatment.
Keywords: temporal bone; fracture in the base of skull; computed tomography by X-ray